2011
DOI: 10.1111/j.1600-6143.2011.03614.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation With a New Therapeutic Oxygen Carrier Reduces Chronic Fibrosis and Organ Dysfunction in Kidney Static Preservation

Abstract: † Both the authors have equally contributed to this work.Static preservation is currently the most widely used organ preservation strategy; however, decreased donor organ quality is impacting outcome negatively. M101 is an O 2 carrier with high-oxygen affinity and the capacity to function at low temperatures. We tested the benefits of M101 both in vitro, on cold preserved LLC-PK1, as well as in vivo, in a large white pig kidney autotransplantation model. In vitro, M101 supplementation reduced cold storage-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 64 publications
3
65
1
2
Order By: Relevance
“…The M101 product also has high oxygen affinity (P 50 ~ 7 mm Hg) and high oxygen carrying capacity; carrying up to 156 oxygen molecules per hemoglobin. It is active over a wide range of temperatures 12 and has a half-life, determined using M101 tagged with fluorescent dye, of age 3 of 39 4 ~24 h in rats. 13 M101 has been shown to improve organ preservation 12,14 and a recent study, measuring arterioles and venules in the hamster dorsal skin fold, reports that M101 does not have vasoconstrictive properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M101 product also has high oxygen affinity (P 50 ~ 7 mm Hg) and high oxygen carrying capacity; carrying up to 156 oxygen molecules per hemoglobin. It is active over a wide range of temperatures 12 and has a half-life, determined using M101 tagged with fluorescent dye, of age 3 of 39 4 ~24 h in rats. 13 M101 has been shown to improve organ preservation 12,14 and a recent study, measuring arterioles and venules in the hamster dorsal skin fold, reports that M101 does not have vasoconstrictive properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is active over a wide range of temperatures 12 and has a half-life, determined using M101 tagged with fluorescent dye, of age 3 of 39 4 ~24 h in rats. 13 M101 has been shown to improve organ preservation 12,14 and a recent study, measuring arterioles and venules in the hamster dorsal skin fold, reports that M101 does not have vasoconstrictive properties. 10 These product characteristics and pharmacodynamic data make M101 a candidate for further development for pre-hospital treatment for TBI if the product 1) does not cause cerebral arteriolar vasoconstriction (safety) and 2) shows evidence of reducing brain injury (efficacy) in TBI models.…”
Section: Introductionmentioning
confidence: 99%
“…SCOT15, which belongs to these fourth-generation solutions, combines an extracellular-like composition with a 20-kDa PEG and is known for its cell-protection capacity and immunocamouflage properties [13,31,32]. Although insufficient data are currently available to provide guidelines on preservation solutions for pediatric kidney transplantation, numerous preclinical studies have shown the potential of modifying preservation solutions to improve graft survival [33][34][35].…”
Section: Pediatric Organ Donors and Their Managementmentioning
confidence: 99%
“…Cette approche a montré des bénéfices en clinique, notamment sur les greffons « à critères élargis » (provenant de donneurs ayant des comorbidités) [27]. Des études expérimentales sont en cours pour évaluer de nouveaux concepts et adopter des conditions plus propices au maintien physiologique des tissus par l'oxygénation du milieu de perfusion [28] ou par l'ajout de transporteurs d'oxygène ou de nutriments [29].…”
Section: Conservation Des Greffonsunclassified